TERRORISM CRIMES IN INDONESIA: A COUNTERTERRORISM PERSPECTIVE - Muhammad Hatta; Ramalinggam Rajamanickam; Tengku Noor Azira Tengku Zainudin; Mohd Zamre Mohd Zahir (Universiti Sains Islam Malaysia, 2025)
Malaysian Journal of Syariah and Law, Volume 13 Issue 1 Page (223-235)